Forming machine maintenance planning using the reliability centered maintenance (RCM) method at PT. KHI pipe industries - Yusuf, Yusvardi; Djamal, Nugraheni; Cahyadi, Dadi (Jurnal Teknika, 2024)
PT KHI Pipe Industries is a member of the Krakatau Steel Group which operates in the manufacturing industry. The company's main activity is the production of high quality steel pipes for oil and gas. The problems that occurred were breakdowns 19 times in one year and damage to one of the components on the forming machine. Currently the company is still implementing a Corrective Maintenance system. Based on the problem, maintenance proposals need to be made using the Reliability Centered Maintenance (RCM) method to determine critical components, find out the correct Task Selection (Action Selection), and provide improvement proposals. Based on the results of RCM research, the critical component in the forming machine is the Squeeze Top Roll component which consists of Bearing, Shaft, Sleeve, Cover Sleeve, and Roll Top. Obtained a broken bearing with an RPN value of 378, LTA category B, and Time Directed action selection; broken cover bolt with RPN value of 324, LTA category B, and Condition Directed action selection; rocking roll with an RPN value of 180, LTA category D, and selection of the Finding Failure action; worn shafting with an RPN value of 144, LTA category D, and selection of the Finding Failure action. Proposed improvements for components include making a maintenance schedule according to the component's service life, selecting the NUTR65150H bearing type, modifying the greasing line, carrying out routine checks once a week, and improving the design of the shafting, roll, bearing and top squeeze.